The Analysis of Constraints and Opportunities Development of Livestock in Aceh Besar - Ikramuddin Ikramuddin; Ghazali Syamni; Bambang Ali Nugroho; Nuhfil Hanani (Syiah Kuala University, 2015)
This research aims to analyze the constraints and opportunities of livestock business development in Aceh Besar. The data used in this research is primary data obtained by distributing questionnaires to the related parties such as Animal husbandry in Aceh and Aceh Besar, breeders, breeders association and manager of slaughterhouse. The data analyzed by using SWOT analysis. The research found that the opportunity of livestock development is great enough beside the availability of land, government participation in giving seed (calf) of Aceh cattle to a number of breeders, mowers/feed crusher, vaccination, administration, artificial insemination and land development for forage. In addition, the constraints experienced by cattle breeders are limited which based on the infrastructure, poor management of cattle breeders, lack of cage sanitation, limited forage during dry season, and the demands of industry/manufacture are still dominated by imported beef.